Synthesis and In Vitro Evaluation of Novel Acyclic and Cyclic Nucleoside Analogs with a Thiadiazole Ring - Zhao, Yuxiang (Hindawi Publishing Corporation, 2013)
The synthesis of six thiadiazole nucleoside analogs is reported: 5-diacetylamino-1,2,4-thiadiazol-3-one (1), 5-amino-2- (tetrahydrofuran-2-yl)-1,2,4-thiadiazol-3-one (2), 5-amino-3-[(2′-hydroxyethoxy)methyl]-1,3,4-thiadiazol-2-one (3), 5-amino-3-(4′-hydroxy-2′-hydroxymethyl-butyl)-1,3,4-thiadiazole-2-thione (4), (R)-5-amino-3-(2′,3′-dihydroxypropyl)-1,3,4-thiadiazole-2-thione (5), and (S)-5-amino-3-(2′,3′-dihydroxypropyl)-1,3,4-thiadiazole-2-thione (6). The synthesis, characterization, and properties of these new synthesized thiadiazole derivatives are discussed. A dimerization of 5-amino-3H-1,3,4-thiadiazole-2-thione (14) by sodium nitrite resulting in di-(5-amino-1,3,4-thiadiazol-2-yl) disulfide (19) is also reported. The preliminary in vitro evaluation of these newly synthesized compounds is discussed.